Problematika dalam Pelaksanaan Kurikulum Merdeka pada Pembelajaran IPS Siswa Kelas VII Di SMPN 1 Pasaman - Dirmaya, Oktira; Rahayu, Sri; Akbar, Waza Karia (FKIP Universitas Wisnuwardhana, 2024)
This study aims to describe the problems in implementing the independent curriculum in social studies learning for class VII at SMPN 1 Pasaman. This study uses a descriptive qualitative research method. Data collection is carried out using observation, interview and document study methods. The technique used in determining informants in this study is the Purposive Sampling technique. The results of this study are that there are problems in implementing the independent curriculum, namely 1) Lack of Socialization Regarding the Independent Curriculum Which Resulted in Minimal Teacher Understanding Regarding the Differences in Learning in the Independent Curriculum with K13, 2) Lack of Teacher Creativity in Using Learning Methods and Media in Social Studies Learning, 3) Implementation of Diagnostic Assessments that are not Optimal at SMPN 1 Pasaman, 4) Lack of mastery of Material by Students for Social Studies Subjects so that it is difficult to implement formative and summative assessments, 5) Problems in Implementing the P5 Program (Pancasila Student Profile Strengthening Project).